The tadpole of Boana stellae (Anura: Hylidae) - Widholzer, Ronaldo Libardi; Castroviejo-Fisher, Santiago (Zootaxa, 2018)
Boana stellae (Kwet, 2008) was allocated within the B. pulchella species group and, presumably, is closely related to B. caipora (Antunes, Faivovich, and Haddad, 2008), B. curupi (Garcia, Faivovich, and Haddad, 2007), B. joaquini (Lutz, 1968), and B. semiguttata (Lutz, 1925) due to the similarity of the external morphology of adult specimens (Kwet 2008). Boana stellae is currently only known from adult specimens and embryos from the type locality in Rio Grande do Sul, southeastern Brazil, and from a single locality in Misiones, Argentina (Ferro et al. 2018). Although the embryo morphology has been described in detail (Navarro Acosta et al. 2017; Navarro Acosta & Vera Candioti 2017, as Hypsiboas sp. gr. pulchellus), the tadpole of B. stellae has not been yet described.